Foundation Doctors’ Exposure to Interventional Radiology in Two Large Teaching Hospitals in the United Kingdom - Zaid Alsafi; Sanjeev Ramachandran; Vamsee Bhrugubanda; Alison Graham; Ali Alsafi (The Arab Journal of Interventional Radiology, 2020)
Background: Significant efforts have been made to improve medical students' exposure to interventional radiology (IR). Foundation doctors in the UK, however, are a neglected group, with little being done engage these doctors who are at a crucial juncture in their training. Objectives: The objective of the study is to assess Foundation Year 1 (FY1) doctors' understanding of and exposure to IR. Methods: FY1s from two teaching hospitals in the UK at the end of their first year of Foundation training were invited to take part in an 18-question survey, including 14 single-best-answer (SBA) questions. The questions examined knowledge of IR and other specialties. The SBAs were scored out 14 and the Student's t-test was used to compare IR and non-IR scores. Results: Questionnaires were given to 72 FY1 doctors and 52 (72.2%) were completed. The median score was 9/14 (64.3%) [4.5/14–12/14]. Questions relating to coronary intervention and neurosurgery scored best (96.2% and 94.3%, respectively). The mean score for IR-related questions was significantly lower than that for non-IR questions (51.5% vs. 81.1%, respectively, P < 0.0001). Participants who referred patients to IR at least once per month scored higher than those who rarely referred (60.5% vs. 47.2%, respectively, P < 0.0084). Nearly 83.0% of participants expressed a desire to gain more exposure to IR. Conclusion: Although Foundation doctors have some understanding of IR, reflecting some exposure to the specialty, this remains deficient when compared with their knowledge of other specialties. This may be improved by the introduction of IR specific teaching during the Foundation program.